Members of the Teamsters Union show their support - Manuel Echavarria:::photographer::: (2025)
Members of the Teamsters Union from Santa Maria show their support during a visit by Cesar Chavez to the Santa Maria Valley. The International Brotherhood of Teamsters would later turn their backs on the UFW when members signed sweet heart contracts with local growers to avoid bargaining with the UFW. Miembros de The Teamsters Union de Santa Maria (Unión de Traileros) declararon solidaridad durante una visita de Cesar Chavez al Valle de Santa Maria. La International Brotherhood of Teamsters (Hermandad Internacional de Traileros) traicionó a la UFW y firmó un contrato con los agricultores locales para evitar negociaciones con la UFW.